FORMULASI PELEMBAB BIBIR ALAMI DARI SARI BUAH JERUK KALAMANSI (Citrofortunella microcarpa) DAN EKSTRAK BUNGA ROSELLA (Hibiscus sabdariffa) - Dwi Dominica; Delia Komala Sari; Dian Handayani; Dinda Zulkarnain; Anggi Triphosa Simanjuntak; Dinah Khairunisah; Fahma Shufyani (Journal of Pharmaceutical and Sciences, 2023)
Background : Exposure to UV rays from the sun can damage the lip keratin cells which protect the lips. The cosmetic used to moisturize the lips is lip balm. One of the natural ingredients that contain high antioxidants are Kalamansi oranges and rosella flowers. This study aims to make Lip Balm preparations with a concentration of F1 4% of calamansi orange juice, F2 with a concentration of 5% of rosella flower extract, F3 with a combination of calamansi orange juice and rosella flower extract. Flower extraction was obtained by maceration using ethanol. The experimental method was used in this study, and the physical stability of the lip balm was carried out for approximately 4 weeks. The results of testing the physical properties of the calamansi citrus juice and rosella flower extract have a homogeneous composition, have a pH range of 6.0-6.3, have a melting point of 51-54 ℃, and are stable in storage for 28 days, that is, there is no change on texture, aroma, taste, and color. Has a percent increase in lip moisture F0, F1, F2, and F3 respectively, namely 48.5%, 59.1%, 130.7%, and 136.4%. In this study, continued with the analysis using SPSS version 24, the value of p <0.05 was obtained at 84 hours. The conclusion is that calamansi orange juice and rosella flower extract can be formulated in the manufacture of lip balm with various concentrations.